Complications and Mortality After Percutaneous Endoscopic Gastrostomy in Geriatrics: A Prospective Multicenter Observational Trial - Wirth, Rainer; Voss, Christian; Smoliner, Christine; Sieber, Cornel; Bauer, Jürgen; Volkert, Dorothee (Journal of the American Medical Directors Association, 2012)
Background: Generally, the high short-term mortality after percutaneous endoscopic gastrostomy (PEG) in geriatric patients is attributed to the severity of their underlying diseases. However, the procedure-related mortality in this group is unknown.Methods: This prospective multicenter observational study gathered information about 197 geriatric patients treated with PEG insertion, including the indication for PEG insertion and the prevalence of postprocedure complications and analyzed how these factors related to mortality.Results: Dysphagia (64%) and insufficient food intake (76%) were the most frequent indications for PEG insertion. Severe complications after PEG insertion occurred in 9.6% of patients. Mortality was 9.6% in hospital, as well as 18.4% at 1 month. Six months after PEG placement, with 81 patients lost to follow-up, mortality was 51.9%. Hospital mortality was significantly higher in patients with severe complications caused by PEG insertion (47.4% vs 5.6%; P < .001). A regression analysis that corrected for confounding factors revealed that severe complications in general (HR 6.9; 95% CI: 2.6-18.1; P < .001), peritonitis (HR 33.1; 95% CI: 3.7-293.2; P = .002), and severe wound infections (HR 6.9; 95% CI: 1.9-24.9; P = .003) were each independently associated with hospital mortality. Considering the prevalence of procedure-related complications and their association with early mortality after PEG insertion, the procedure-related mortality rate in geriatric patients was at least 2% in this study.Conclusion: Although the prevalence of complications after PEG in this study of multimorbid geriatric patients is within the expected range, the procedure-related mortality is higher than expected. Copyright (C) 2012 - American Medical Directors Association, Inc.
Keywords: Complications; elderly; mortality; percutaneous endoscopic gastrostomy; tube feeding